Conceptual Framework of Built Environment Factors on Cycling Behaviour among Residential Neighbourhoods - Haron, Norhazlan; Zainol, Halmi; Wan Omar, Wan Rabiah; Rahman, Norainah Abdul (Universitas Aisyiyah Yogyakarta, 2021)
Cycling as one of a mode of transport in urban and residential areas has been determined as a solution for the urban issue. It is an active and environmentally friendly mode of travel. However, the relationship between the physical built environment cyclingbehaviour among residential are less associated with increasing the bike-ability of residents. The main factors as a major contributor to bike-ability behaviour are built environment and social factors. The main aspect to determine the interaction between all the factors will be based on the behaviour of individuals and their personal characteristics. The new conceptual framework of bike-ability behaviour was discovered in assisting and producing cycling behaviour within neighbourhoods.Â